ANALYSIS OF CROSS CULTURAL LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEE LOYALTY THROUGH JOB SATISFACTION AS MEDIATION VARIABLES - Herwanto, Bayu Marga Nurmaulana; Danial, Deni Muhammad; Ramdan, Asep Muhamad (DIA: Jurnal Administrasi Publik, 2025)
In the era of globalization, manufacturing companies face challenges in maintaining employee loyalty amidst cultural diversity. The phenomenon of low employee loyalty is evident from high turnover rates, absenteeism, and non-compliance with company regulations. This study aims to analyze the influence of cross-cultural leadership and organizational culture on employee loyalty, with job satisfaction as a mediating variable in the manufacturing industry in Cianjur Regency. The method used is descriptive analysis with a population of 8,400 employees. The sample selection was carried out randomly and analyzed using Structural Equation Modeling (SEM) with a sample size of 200 respondents. The results of the study indicate that cross-cultural leadership does not have a significant direct effect on employee loyalty, but it has a significant impact on job satisfaction. Organizational culture has a significant effect on both employee loyalty and job satisfaction. Job satisfaction is proven to mediate the effect of cross-cultural leadership and organizational culture on employee loyalty. These findings underscore the importance of leadership that can manage cultural diversity and a positive organizational culture in creating job satisfaction, ultimately enhancing employee loyalty. This research provides insights for manufacturing companies in Cianjur to focus on leadership and organizational culture aspects to improve employee loyalty through job satisfaction.